Analysis of Tuberculosis Prevention Behavior: The Role of Knowledge and Attitude in Bantul - Liena Sofiana; Risma Aolia Putri; Marsiana Wibowo; Ardyawati Wira Oktaviana; Erni Gustina; Suci Musvita Ayu (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: Tuberculosis is the leading cause of mortality and morbidity. When an infected individual coughs or sneezes without using a mask or personal protective equipment, transmission occurs, resulting in a rise in TB cases. This is significant because without sufficient measures by the diseased individual, the chance of disease transmission increases. This study aims to evaluate the link between knowledge, attitudes, and behaviour in avoiding TB transmission in the Bantul Health Service Work Area. Methods: This is an analytical observational study using a cross-sectional research methodology. This research included 55 TB patients still being treated at the Health Center of the Bantul Health Service Work Area. This study used a comprehensive sample approach. Data was obtained via a questionnaire, and the results were analyzed using chi-square, logistic regression, and Rasch models. Results: Knowledge (sig: 0.003; OR: 10.334) and attitudes (sig: 0.029; OR: 4.938) are associated with TB prevention behaviour in the Bantul Health Service Work Area. The most manageable behaviour to avoid transmission to those around them is taking medicine regularly and eating healthy food (logit: -2.10), while the most challenging activity is opening the home window (logit: 1.96). Conclusion: Knowledge and attitude are risk factors for preventing TB transmission, thorough education about tuberculosis prevention is required through multiple health promotion media.